PGATA: A Positive Selection Vector Based on the Toxicity of the Transcription Factor GATA-1 to Bacteria. (April 1996) - Trudel, P.; Provost, S.; Massie, B.; Chartrand, P.; Wall, L.
The transcription factor GATA-1 is a zinc finger DNA-binding protein essential for the development of red blood cells. When we expressed different regions of the zinc finger domain in bacteria using an isopropyl-β-D-thiogalactoside (IPTG) inducible systgm, growth of bacteria harboring the active DNA-binding domain of GATA-I was rapidly inhibited upon IPTG induction. The growth inhibition pattern suggested it may be occurring at the level of the initiation of replication, and GATA-1 was found to bind to three of the four DNA A protein-binding sites in the origin of replication. This toxicity was used to develop a positive selection vector system in which cloned DNA fragments interfered with the production of the GATA-1 DNA-binding domain. Thus, vector molecules containing the insert of interest are selected for when bacteria are grown in the presence of IPTG. Wth this system, the vector does not need to be dephosphorylated, purified or completely digested with a restriction enzyme for the eficient cloning of DNA fragments even when the vector-to-insert DNA molar ratio in ligation reactions is 10 to 1. Moreover, no special strain of Escherichia coli is required, and the selection might also be applicable to other species of bacteria if the toxicity of GATA-1 relates to inhibition of the DNA A protein.